Dinamika Tata Kelola Hutan: Potret Penerapan Kebijakan Reforma Agraria dan Perhutanan Sosial di Taman Nasional Kerinci Seblat - Bayu Budiandrian; Ahmad Jaetuloh; Pramasty Ayu Koes Dinar (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2022)
After the decision of the Constitutional Court No. 35 of 2012 concerning Customary Forests, the status of customary forests under the state authority now has been removed from State forest areas and now customary law communities are given the authority to re-manage their customary forests through government permits. However, there are still many Customary Law communities who have not finished yet and succeeded in fighting for their own forests, one of which is the Rejang community in Lebong Regency, Bengkulu. The Agrarian Reform and Social Forestry (RA/PS) policy is mentioned in the 2014-2019 RPJMN. The policy allocates 12.7 million hectares of forest area for Social Forestry and 9 million hectares as Land for Agrarian Reform Objects (TORA). However, agrarian reform and social forestry policy certainly required broader political, economic and cultural changed which is did not seen yet at the local and regional levels. In Lebong Regency, the Rejang Customary Law Community still has to continue to fight to reclaim their rights to the Customary Forest. For this reason, this study seeks to provide an overview of how the practice of implementing agrarian reform and social forestry policies in the Kerinci Seblat National Park. This study used data collection method by in-depth interviews and direct observation as well as focus group discussion (FGD). The total number of respondents in this study were 35 respondents. The results of this study indicate there is a dualism in forest management in Kerinci Seblat National Park between the State and the Customary Law Community. In addition, the management of the Rejang Indigenous Forest cannot be separated from the governance of the kuteui or the institutions of the indigenous peoples themselves; common property. In the forest which they call “Demong Samin”, there are at least 2 (two) classifications of rights attached to the Kuteui residents, namely property and owner.